Germanizmy bydgoskie na tle polsko-niemieckich kontaktów językowych (Conversatoria Linguistica, 2018)
Polish-German language contacts, which will be considered one-way – we are talking about German borrowings in Polish – are among the most important traces of contacts between Polish culture and German culture.Bydgoszcz Germanisms in the context of Polish-German language contacts An interesting illustration of centuries-old Polish-German language contacts are the urban toponyms of German provenance, associated with the castle on the Brda River from its earliest history. The location of the city was the basis for its German name Bromberg, whose origins date back to the 14th century, when Bydgoszcz was conquered by the Teutonic Knights. Many Germanisms in Bydgoszcz dialect are words that are the names of streets, parks, or urbanonyms, but also those belonging to different dialects and folk dialects.